2016
DOI: 10.5535/arm.2016.40.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hippotherapy on Psychosocial Aspects in Children With Cerebral Palsy and Their Caregivers: A Pilot Study

Abstract: ObjectiveTo investigate the effects of hippotherapy on psychosocial and emotional parameters in children with cerebral palsy (CP) and their caregivers.MethodsEight children with CP were recruited (three males and five females; mean age, 7.3 years; Gross Motor Function Classification System levels 1–3). Hippotherapy sessions were conducted for 30 minutes once weekly for 10 consecutive weeks in an indoor riding arena. The Gross Motor Function Measure (GMFM), Pediatric Balance Scale (PBS), and the Korean version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
(27 reference statements)
0
8
0
5
Order By: Relevance
“…Interestingly, this result validated the suspicion of a positive relationship between the changes in the psychological QOL, particularly in the “positive feeling,” of caregivers and improvement in the children's gait functions after hippotherapy. Conversely, several reports have shown that the health-related QOL of caregivers is not necessarily associated with their children's level of functioning (35) or with improvements in their level of performance (23). Although the sample size in our study was small, which may have restricted the interpretation of our results, it is conceivable that hippotherapy may provide better psychological QOL within the family caregivers of children with CP by recognizing their children's gait function improvements through successful horseback-riding sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this result validated the suspicion of a positive relationship between the changes in the psychological QOL, particularly in the “positive feeling,” of caregivers and improvement in the children's gait functions after hippotherapy. Conversely, several reports have shown that the health-related QOL of caregivers is not necessarily associated with their children's level of functioning (35) or with improvements in their level of performance (23). Although the sample size in our study was small, which may have restricted the interpretation of our results, it is conceivable that hippotherapy may provide better psychological QOL within the family caregivers of children with CP by recognizing their children's gait function improvements through successful horseback-riding sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, hippotherapy currently lacks a scientific basis for how it improves the QOL of these caregivers. Several earlier reports have suggested that hippotherapy motivates children to actively participate in social activities (5, 21); however, no psychological or emotional improvements in the QOL of mothers of children with CP have been demonstrated in small observational studies (22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…Five items were positively worded and five were negatively worded. Items were summed with the negatively worded items reverse-coded to produce a self-esteem score from 0 to 30 (with higher scores indicating higher self-esteem) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…A equoterapia é uma estratégia de intervenção para melhora da funcionalidade de crianças com PC, uma vez que elas necessitam de tratamento contínuo, repetitivo e com estímulos diversos [6,7]. Como técnica de reabilitação, é uma modalidade facilitadora, lúdica e recreativa, que possibilita realizar movimentos, que muitas vezes se torna difícil de realizar no solo, e estimulando para que o paciente tenha uma melhor qualidade de vida [8].…”
Section: Introductionunclassified